2015
DOI: 10.1016/j.electacta.2015.01.183
|View full text |Cite
|
Sign up to set email alerts
|

Factors Controlling Stress Generation during the Initial Growth of Porous Anodic Aluminum Oxide

Abstract: Keywords:anodizing stress oxide nanotube porous anodic oxide self-ordered porous oxide A B S T R A C T Anodic oxidation of reactive metals such as Al and Ti produces oxide films with self-organized arrangements of nanoscale pores. Stress-driven mass transport of oxide is considered to play an important role in pore formation and self-ordering. Using in situ stress monitoring during both anodizing and subsequent open-circuit oxide dissolution, distributions of in-plane residual stress were measured in anodic al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 45 publications
(84 reference statements)
3
27
0
Order By: Relevance
“…The main panel of Figure 2 shows the force per width measured in a typical experiment, in which anodizing was followed by opencircuit dissolution of the oxide in the anodizing bath. Consistent with results in other papers, anodizing at 5 mA/cm 2 produces a compressive force that increases with time during barrier oxide growth [18,20,21,35]. The force per width change measured during anodizing will be referred to as the "anodizing force."…”
Section: Evolution Of Stress Distributions During Barrier Oxide Growthsupporting
confidence: 62%
See 4 more Smart Citations
“…The main panel of Figure 2 shows the force per width measured in a typical experiment, in which anodizing was followed by opencircuit dissolution of the oxide in the anodizing bath. Consistent with results in other papers, anodizing at 5 mA/cm 2 produces a compressive force that increases with time during barrier oxide growth [18,20,21,35]. The force per width change measured during anodizing will be referred to as the "anodizing force."…”
Section: Evolution Of Stress Distributions During Barrier Oxide Growthsupporting
confidence: 62%
“…The interface force at the different anodizing potentials is compiled in Figure 3, The stress in this layer was tensile at small thickness, but became increasingly compressive at higher voltage, reaching levels of -2 to -4 GPa above 60 V. Elsewhere, we showed that near-surface tensile stress at low voltage is produced by the initial application of anodizing current, and seems to result from electric field-induced transfer of anions into the interior of the oxide [35]. As the voltage increases, this tensile nearsurface stress is increasingly masked by the compressive oxide stress introduced by anodizing [39].…”
Section: Evolution Of Stress Distributions During Barrier Oxide Growthmentioning
confidence: 86%
See 3 more Smart Citations